Compliance Analysis Of Taxable Entrepreneurs In Manado City - IBRAHIM, Lisna; MORASA, Jenny (PT Keberlanjutan Strategis Indonesia, 2023)
Taxes are a source of state financing that contributes greatly in carrying out state development for the welfare of all Indonesian people. The application of the self-assessment system plays a role in tax collection and has a very important role. Taxpayers have the trust, responsibility and authority to calculate, pay and report taxes. Taxpayers who have a Taxpayer Identification Number are expected to be active in fulfilling their obligations. This study aims to determine taxpayer compliance, especially Taxable Entrepreneurs in carrying out their tax obligations. The method used is a qualitative research method. The results of the study show that in fulfilling tax obligations Taxable Entrepreneurs does so based on applicable regulations and fulfills the specified conditions, namely registering as a taxpayer, submitting SPT on time, making correct reporting, and not having tax arrears. However, in carrying out their tax obligations, Taxable Entrepreneurs still has obstacles such as the busy network of the Directorate General of Taxes (DGT) which makes it difficult to access, besides that the lack of understanding of taxes is also an obstacle they face. To overcome obstacles in the form of a network, taxpayers try to fulfill their tax obligations before the specified deadline to avoid the DGT's network being busy. As for the lack of understanding, taxpayers use the services of a tax consultant to occasionally ask questions and assist them in carrying out their tax obligations.